TRANSLATION PROBLEMS IN A NEW TECHNOLOGICAL SPHERE - Abdyrakmatova N. К.; Sandybaeva A. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
This article is dedicated to a comprehensive study of translation issues in the context of the new technological environment. The possibilities of machine translation tools such as Google Translate and ChatGPT are examined for their ability to adequately convey the content, meaning, and emotional depth of literary works. The development of digital technologies in the 21st century and the widespread use of artificial intelligence have a significant impact on the field of translation, improving work efficiency, but at the same time causing problems related to the loss of emotional, cultural, and lexical features of the text. The article provides a detailed comparison of machine and human translation, their advantages and disadvantages. It also addresses the important issue of preserving cultural, lexical, and semantic features when translating literary works, as well as their significance for a global audience and intercultural communication, making this process relevant and multifaceted.